THE EFFECT OF ADAPTIVE WORK BEHAVIOR, SELF EFFICACY, EMPLOYEE COMPETENCE AMD JOB SATISFACTION ON THE PERFORMANCE OF BKPP BANYUWANGI - Aliya, Ikfina Himmati; Riyanto Setiawan; Amalina Maryam Zakiyyah (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the influence of adaptive work behavior, self-efficacy, employee competence, and job satisfaction on the performance of employees of the Banyuwangi Civil Service, Education, and Training Agency (BKPP). In the context of personnel services, BKPP has an important role in managing personnel administration and developing the competence of state civil servants (ASN). However, there are challenges in optimizing the digital service system through the SILAKAN application, especially due to age gaps and generational differences among employees. Method: This study uses a quantitative approach with an explanatory research design, where the research sample consisted of 98 respondents taken using a saturated sampling technique. Data were analyzed using multiple linear regression through SPSS 25.0. Results: The results showed that all variables, namely adaptive work behavior, self-efficacy, employee competence, and job satisfaction, had a significant effect on the performance of BKPP Banyuwangi employees. Novelty: This study offers novelty by integrating four variables simultaneously to provide a more comprehensive understanding of the factors that influence employee performance. In addition, this study also highlights the importance of the influence of technology in the personnel service system, which has not been widely discussed in the related literature. It is hoped that the results of this study can contribute to the development of strategies to improve employee performance through an approach based on organizational behavior and technological innovation.